23/#722 Procedural interventions for oligoprogression during treatment with immune checkpoint blockade in gynecologic malignancies. (4th December 2022) - Sia, Tiffany; Wan, Vivian; Zivanovic, Oliver; Sonoda, Yukio; Chi, Dennis; Roche, Kara Long; Jewell, Elizabeth; Tew, William; O'Cearbhaill, Roisin; Cohen, Seth; Makker, Vicky; Liu, Ying; et al.
Abstract : Objectives: To evaluate feasibility and outcomes of procedural interventions for oligoprogressive disease among patients with gynecologic cancer treated with immune checkpoint blockade (ICB). Methods: Patients with gynecologic cancers treated with ICB between 1/2013–10/2021 who underwent procedural interventions including surgical resection (OR), interventional radiology ablation (IR), or radiation therapy (RT) for oligoprogressive disease were identified. Procedures performed before ICB initiation, or ≥6 months (mos) after ICB completion were excluded. Long ICB duration prior to intervention was defined as ≥6 mos. PFS and OS were calculated from procedure date until disease progression or death, respectively. Results: During the study period, 887 patients received ICB. Among patients with oligoprogressive disease, 41 underwent procedural intervention: 10 OR, 3 IR, and 28 RT. Primary tumor type included uterine (74%) and ovarian (23%). ICB regimen included PD-1/PD-L1 inhibitor (46%), PD-1/PD-L1 inhibitor + tyrosine kinase inhibitor (29%), PD-1/PD-L1 inhibitor + CTLA-4 inhibitor (12%), and PD-1/PD-L1 inhibitor + other (12%). Sites of oligoprogression included abdomen (32%), lung (17%), bone (17%), distant lymph node (17%), and vagina (10%). Subsequent treatment included continuation of same therapy (49%), other ICB (10%), or chemotherapy (29%). Short vs long ICB duration pre-procedure demonstrated median PFS of 9.2mos versus 5.6mos, and median OS of 36.1mos and 22.0mos, respectively. Conclusions: Procedural interventions for patients with oligoprogression on ICB are feasible and demonstrate favorable outcomes. Early intervention appears to associate with prolonged PFS & OS. With expanding use of ICB, it is important to investigate combined modalities to maximize therapeutic benefit for patients with gynecologic cancers.